2019
DOI: 10.1186/s11658-019-0147-z
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin receptor depletion suppressed hCG-induced testosterone expression in mouse Leydig cells

Abstract: Melatonin receptors MT1 and MT2 (genes officially named MTNR1A and MTNR1B, respectively) play crucial roles in melatonin-mediated regulation of circadian rhythms, the immune system, and control of reproduction in seasonally breeding animals. In this study, immunolocalization assay showed that MT1 and MT2 are highly expressed in Leydig cell membrane. To understand the biological function of melatonin receptors in hCG-induced testosterone synthesis, we generated melatonin receptor knockdown cells using specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Also, relatively short-term (11 days) exposure to inhibitory photoperiods has been shown to induce local and location-specific changes in androgen receptor expression. An inverse relationship between melatonin synthesis and testosterone levels has also been reported in mouse Leydig cells and involves melatonin receptors regulating hCG-induced testosterone synthesis (Gao et al 2019). This information could be important in explaining how day length modifies gonadal steroid hormones and an interaction between testosterone and photoperiod can add to our understanding of environmental regulation of neuroendocrine function.…”
Section: The Role Of Circadian System In Male Reproductive Biologymentioning
confidence: 64%
“…Also, relatively short-term (11 days) exposure to inhibitory photoperiods has been shown to induce local and location-specific changes in androgen receptor expression. An inverse relationship between melatonin synthesis and testosterone levels has also been reported in mouse Leydig cells and involves melatonin receptors regulating hCG-induced testosterone synthesis (Gao et al 2019). This information could be important in explaining how day length modifies gonadal steroid hormones and an interaction between testosterone and photoperiod can add to our understanding of environmental regulation of neuroendocrine function.…”
Section: The Role Of Circadian System In Male Reproductive Biologymentioning
confidence: 64%
“…In contrast to the previous studies, in 2018 Deng et al reported that melatonin increases testosterone secretion in Leydig cell when were concurrently cultured with Sertoli cells, as well as increase in the expression of RORα gene 29 . Another study on a Leydig cancer cell line showed that suppression of melatonin receptors, MT1 and MT2, stopped the genes in the testosterone synthesis pathway 30 . These con icting results require closer attention especially considering that in our study when melatonin was concurrently administered with brin scaffold and LED green light, the genes involved in proliferation and also the genes involved in steroidogenesis were highly expressed; concluding that a 3D system would have lessened the inhibitory effects of melatonin on cell proliferation and testosterone production.…”
Section: Discussionmentioning
confidence: 99%
“…When the melatonin receptors, especially receptor 1A, were knocked down, the decrease of the testosterone levels was observed. There was also a decrease of the steroidogenic gene expression—CYP type 11A1 and type 17A1 [ 83 ].…”
Section: Potential Drug Targets and Active Substances In Novel Thementioning
confidence: 99%